Effects of intermittent cycles of ischemia with resistance and endurance training on Murf-1 and Atrogin-1 gene expression and fiber diameter of gastrocnemius muscle in diabetic rats - Majid Zatparvar; Amin Farzaneh Hesari; Parvin Farzanegi (فیزیولوژی ورزش و فعالیت بدنی)
Background and Purpose: Muscular atrophy is one of the most common complications of diabetes. Exercise training has been suggested as one of the treatment strategies for muscular atrophy in diabetes. Intermittent cycles of ischemia (ICI) protects tissues from subsequent ischemic injury. However, whether ICI has beneficial effects on diabetic atrophy remains unknown. The present study aimed to investigate the synergistic effect of ICI with resistance and endurance training on Murf-1 and Atrogin-1 gene expression and fiber diameter of the gastrocnemius muscle in diabetic rats.Materials and Methods: In this experimental research, 42 wistar rats (age, 8 weeks; weight, 228.31±12.1 gr) were randomly divided into seven groups of normal control (C), diabetic (D), diabetic ischemic (I), diabetic resistance training (R), diabetic endurance training (E), diabetes ischemic+resistance training (IR), diabetes ischemic+endurance training (IE). Diabetes was induced by one-step intraperitoneal injection of STZ (50 mg/kg). ICI was conducted by tightening a tourniquet (with a width of 8 mm) around the upper thighs 20 min before exercise and included three 5-min cycles of ischemia, followed by 5 min reperfusion. The training groups performed exercise training for six weeks, five days a week. Resistance training included climbing a ladder by attaching a weight to rats’ tails at 60% of maximum voluntary carrying capacity (14 repetitions with one minute rest between repetitions). Endurance training involved running on a treadmill. The treadmill speed for the first week was set at 9 meters per minute for 15 minutes. By the sixth week, the training speed was increased to 18 meters per minute for 30 min. Murf-1 and atrogin-1 gene expression were measured by RT-PCR and the diameter of fibers of gastrocnemius muscle through the staining with hematoxylin and eosin methods. Data were analyzed by using two-way analysis of variance and Bonferroni’s post-hoc tests.Results: Murf-1 and Atrogin-1 gene expression significantly increased and fiber diameter of gastrocnemius muscle decreased in D group compared to C group (p=0.0001). Murf-1 and atrogin-1 gene expression decreased significantly in R (p=0.0001, p=0.0001), E (p=0.0001, p=0.0003), IR (p=0.0001, p=0.0001) and IE (p=0.0001, p=0.0001) compared to the C group. In addition, muscle fiber diameter increased significantly in R (p=0.034), E (p=0.007), IR (p=0.0003) and IE (p=0.0003) compared to the C.Conclusion: Based on decreases in Murf-1 and Atrogin-1 gene expression and increases in muscle fiber diameter. It could be concluded that aerobic and resistance exercise with intermittent cycles of ischemia are more effective than any of the exercise interventions alone in preventing muscular atrophy in diabetic rats.